2017
DOI: 10.1016/j.tins.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling and Exploiting Astrocyte Dysfunction in Huntington’s Disease

Abstract: Astrocytes are abundant within mature neural circuits and are involved in brain disorders. Here, we summarise our current understanding of astrocytes and Huntington’s disease (HD) with a focus on correlative and causative dysfunctions of ion homeostasis, calcium signaling, and neurotransmitter clearance, as well as on the use of transplanted astrocytes to produce therapeutic benefit in mouse models of HD. Overall, the data suggest astrocyte dysfunction may be an important contributor to the onset and progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 123 publications
(194 reference statements)
7
147
0
Order By: Relevance
“…To our knowledge, the discovery that μ-crystallin is specific for striatal astrocytes provides the first molecular marker that defines a region-specific astrocyte population. Moreover, striatal astrocytes are known to be altered in Huntington’s disease (HD) (Khakh et al, 2017) and μ-crystallin levels decrease in humans and mouse models of HD (Francelle et al, 2015). Interestingly, six of the top 40 striatal enriched astrocyte genes are histones, which is consistent with the GSEA results that chromosome structure-related gene sets were striatal enriched.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the discovery that μ-crystallin is specific for striatal astrocytes provides the first molecular marker that defines a region-specific astrocyte population. Moreover, striatal astrocytes are known to be altered in Huntington’s disease (HD) (Khakh et al, 2017) and μ-crystallin levels decrease in humans and mouse models of HD (Francelle et al, 2015). Interestingly, six of the top 40 striatal enriched astrocyte genes are histones, which is consistent with the GSEA results that chromosome structure-related gene sets were striatal enriched.…”
Section: Discussionmentioning
confidence: 99%
“…It is beyond the scope of this review to list all their described functional changes and contributions to specific diseases. Readers are referred to recent reviews on astrocytes in HD (Khakh et al, ), AD (Chun & Lee, ; Osborn, Kamphuis, Wadman, & Hol, ; Perez‐Nievas & Serrano‐Pozo, ), MS (Wheeler & Quintana, ), SCI (Adams & Gallo, ; Sofroniew, ), TBI (Burda, Bernstein, & Sofroniew, ), stroke (Pekny et al, ), and epilepsy (Coulter & Steinhauser, ; Robel & Sontheimer, ). In general, deficits in normal astrocyte functions are reported and the existence of “killer astrocytes” releasing toxic molecule(s) was even proposed in amyotrophic lateral sclerosis [ALS, (Haidet‐Phillips et al, ; Nagai et al, )] and other neurodegenerative diseases [(Liddelow et al, ), see Section 5].…”
Section: Do Reactive Astrocytes Do Good Things?mentioning
confidence: 99%
“…It has been shown that there is a strong correlation between the length of the repeat and the age of onset (Brinkman, Mezei, Theilmann, Almqvist, & Hayden, ). Pathologically, HD is characterized by a bilateral atrophy of the striatum accompanied by thinning of the motor cortex and neuronal loss in the globus pallidus and corpus striatum (Khakh et al, ; Waldvogel, Kim, Tippett, Vonsattel, & Faull, ). This neurodegeneration is thought to be caused by the accumulation of misfolded mutant huntingtin (mhtt), encoded by HTT bearing the CAG triplet expansion, in neurons of the striatum and more specifically in spiny motor neurons (DiFiglia et al, ; Gutekunst et al, ).…”
Section: Ipscs Derived Astrocytes As Disease Model: a New Platform Tomentioning
confidence: 99%
“…These aggregates were seen at a similar frequency but were smaller compared to the ones found in neurons (Jansen et al, ). Furthermore, astrogliosis has been observed in HD patients from a very early stage and it has been used as one of the grading parameter for the disease (Khakh et al, ; Vonsattel et al, ). Similarly to other neurodegenerative disorders, active astrocytes are thought to play a double role in the development of the disease by uptaking and processing the mhtt aggregates but also by inducing an inflammatory state that may be toxic for neurons.…”
Section: Ipscs Derived Astrocytes As Disease Model: a New Platform Tomentioning
confidence: 99%